Rekonstruksi Perlindungan Hak Milik Perempuan: Telaah Kontradiksi Kawin Mokondo dan Tradisi Jawa Bedah Kutha Boyong Putri - Wahyudi, Misran; Hidayah, Yayuk; Pratiwi, Kurniasari (IN RIGHT: Jurnal Agama dan Hak Azazi Manusia, 2025)
Contemporary millennial society experiences significant shifts in cultural values that affect the institution of marriage. In Javanese tradition, the concept of bedah kutha boyong putri embodies noble values regarding male dignity and responsibility in marriage, emphasizing moral, social, and economic readiness through the criteria of lineage, character, and social standing (bibit, bobot, and bebet). However, the emergence of the “Mokondo” marriage phenomenon in the modern era reflects marital practices that contradict these cultural values and potentially generate social problems and legal vulnerabilities, particularly for women. This article aims to analyze the nature of the contradiction between “Mokondo” marriage practices and the Javanese concept of bedah kutha boyong putri, as well as to examine the legal measures available to women to protect their property rights when marrying a “Mokondo” husband. Employing a socio-legal approach, this study utilizes role theory and contract theory as analytical frameworks. The findings reveal, first, that bedah kutha boyong putri positions men as dignified and responsible actors within marital relationships, whereas “Mokondo” marriages undermine and degrade male roles in the marital structure. Second, prenuptial agreements constitute a strategic legal instrument grounded in the principle of freedom of contract to safeguard women’s property rights prior to marriage. This study underscores the importance of integrating local cultural values with modern legal mechanisms in addressing contemporary challenges to marital justice and gender protection.   Realitas kehidupan masyarakat di era milenial menunjukkan terjadinya pergeseran nilai budaya yang berdampak pada institusi perkawinan. Dalam tradisi Jawa, konsep bedah kutha boyong putri merepresentasikan nilai luhur tentang martabat laki-laki dalam membangun rumah tangga, yang menekankan kesiapan moral, sosial, dan ekonomi melalui kriteria bibit, bobot, dan bebet. Namun, munculnya fenomena kawin “Mokondo” di era kontemporer memperlihatkan praktik perkawinan yang bertentangan dengan nilai budaya tersebut dan berpotensi menimbulkan problematika sosial serta kerentanan hukum, khususnya bagi perempuan. Artikel ini bertujuan menganalisis bentuk kontradiksi antara kawin “Mokondo” dan konsep Jawa bedah kutha boyong putri, serta mengkaji langkah hukum yang dapat ditempuh perempuan untuk melindungi hak miliknya dalam perkawinan dengan suami “Mokondo”. Penelitian ini menggunakan pendekatan sosio-legal dengan pisau analisis teori peran dan teori kontrak. Hasil kajian menunjukkan bahwa, pertama, konsep bedah kutha boyong putri menempatkan laki-laki sebagai subjek yang bermartabat dan bertanggung jawab, sedangkan praktik kawin “Mokondo” justru mendegradasi peran dan posisi laki-laki dalam relasi perkawinan. Kedua, perjanjian perkawinan yang dibuat sebelum perkawinan merupakan instrumen hukum strategis yang selaras dengan prinsip kebebasan berkontrak untuk menjamin perlindungan hak milik perempuan. Temuan ini menegaskan pentingnya integrasi nilai budaya lokal dan mekanisme hukum modern dalam merespons tantangan perkawinan di era milenial.